SAE Technical Paper Series 1985
DOI: 10.4271/850512
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Optimization of the Crashworthiness of a Passenger Vehicle in Frontal Collisions using Response Surface Methodology

Abstract: Although computer simulation is regarded primarily as a tool for systems analysis, simulation can also be used in the process of systems optimization. This paper describes recent enhancements to a computer program package which enables the use of vehicle and occupant simulation models in determining the design of vehicles and restraints for maximum occupant impact protection. Also described is an application of this program package to determine the optimal design of a passenger vehicle involved in frontal coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…For example, Mason et al 3 used response surfaces for a single discipline optimization problem where it was difficult to connect the analysis and optimization codes. Tai et al 4 , Giunta et al 5 , Brown and Nachlas 6 and White et al 7 used response surfaces to satisfy the organizational challenge posed by multidisciplinary optimization, while Mistree et al 8 made extensive use of the fact that response surfaces provide the designer with an overall view of the design space. Also, Van Houten et al 9 showed that response surface methodology is a valuable tool for optimization problems where the designer has to work with functions with non-smooth functional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mason et al 3 used response surfaces for a single discipline optimization problem where it was difficult to connect the analysis and optimization codes. Tai et al 4 , Giunta et al 5 , Brown and Nachlas 6 and White et al 7 used response surfaces to satisfy the organizational challenge posed by multidisciplinary optimization, while Mistree et al 8 made extensive use of the fact that response surfaces provide the designer with an overall view of the design space. Also, Van Houten et al 9 showed that response surface methodology is a valuable tool for optimization problems where the designer has to work with functions with non-smooth functional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…K. Preston White et al describe in [4] recent enhancements to a program which enables the use of vehicle and occupant simulation models to determine the design and restraint systems in order to increase the occupant collision protection, also encompassing an integrated application used to establish the optimal design of a passenger vehicle involved in frontal collisions.…”
Section: Introductionmentioning
confidence: 99%
“…During 1975-78, the Ford Motor Company developed the Safety Systems Optimization Model (Ford Motor Co., 1978), featuring a simulation-optimization program for maximizing a single vehicle's safety performance in frontal crashes. The same program was substantially modified by the University of Virginia in the early 1980s (White, et al, 1985), to include new biomechanical transforms and updated accident data as well as multivariate analysis capability. This model utilized approximating functions to estimate relationships between crash variables due to limitations in computational power at the time.…”
Section: Introductionmentioning
confidence: 99%